Teacher Work Culture In Madrasa - mustofa, dwi rohmadi; Dermawan, Oki (Journal of Advanced Islamic Educational Management, 2022)
The work culture of teachers in madrasa needs to be formed to achieve sustainable changes in the workplace, including increased productivity, so that teachers can have the following: Understanding the basic substance of the meaning of work: attitude towards work and the work environment, behavior when working, work ethics, attitude towards time, and ways or tools used to work. The purpose of this study was to determine the work culture of Madrasa Aliyah teachers in Central Lampung Regency, Indonesia. The research data collected through in-depth interviews, direct observation, and documentation were analyzed through the processes of data reduction, data display, and conclusion or verification. The validity of the data in this study was tested for credibility (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity). According to the findings, teachers' work culture in improving the quality of learning in madrasa aliyah in Central Lampung Regency includes 1) integrity and professionalism. 2) Leadership and exemplary 3) Togetherness and group dynamics 4) Accuracy and speed 5) rationalism and emotional intelligence.